Technological Innovation, Economic Freedom and Environmental Degradation: New Evidence from Time-Varying Causality Analysis in Viet Nam - Quy, Nguyen Thi; Dao, Ha Thi Thieu (International Journal of Energy Economics and Policy, 2025)
Environmental degradation is one of the most serious issues in recent decades, making studying its impact on the economy imperative. Using a novel time-varying Granger causality approach, we examine the causal relationships between real GDP per capita, technological innovation, economic freedom, and trade openness about environmental degradation (measured through carbon dioxide emissions) in Vietnam from 1990 to 2023. The results indicate a significant causal relationship between technological innovation and the control variable of real GDP per capita to emissions throughout the study period. The direct causal relationship between economic freedom and emissions is minimal; however, when economic freedom is combined with technological innovation, a clear causal relationship with emissions emerges. These findings suggest that investment in green technology can improve the state of environmental degradation in Vietnam. Additionally, economic freedom will transfer green technology from developed countries to Vietnam, contributing to a better environment. On the other hand, ensuring that the growth process is linked to sustainable increases in macroeconomic factors is essential to mitigate the adverse effects of real GDP per capita on the environment.